2022
DOI: 10.3390/ijerph19148828
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Circuit Training or Walking Training: Which Program Improves Muscle Strength and Functional Autonomy More in Older Women?

Abstract: To evaluate the effects of two programs (resistance and walking training) on the functional autonomy and muscle strength (isometric and dynamic) of older women, 67 subjects were divided randomly into three groups: resistance training (RTG; Mean = 64.70 ± 6.74 years), walking (WG, Mean = 65.56 ± 7.82 years), and control (CG; Mean = 64.81 ± 4.34). The experimental groups underwent a 16-week intervention. Muscle strength (isometric and dynamic) and functional autonomy were assessed. The subjects participating in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…This study found that resistance circuit training can effectively reduce GDLAM scores in older adults, thereby enhancing their functional autonomy. Among the included studies, high-intensity circuit resistance training has demonstrated a positive impact on functional autonomy, with significant reductions in GDLAM scores in the experimental groups 16 , 48 , 49 .…”
Section: Discussionmentioning
confidence: 99%
“…This study found that resistance circuit training can effectively reduce GDLAM scores in older adults, thereby enhancing their functional autonomy. Among the included studies, high-intensity circuit resistance training has demonstrated a positive impact on functional autonomy, with significant reductions in GDLAM scores in the experimental groups 16 , 48 , 49 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, lower-body strength was improved by the supervised exercise program, regardless of health status (Table 1). In older adults, leg muscle mass (22) and chair stand (36) improve following a remote virtually-supervised exercise program. Better lower-limb strength reduces fall risk (35) and preserves functional autonomy (22,63).…”
Section: Discussionmentioning
confidence: 99%
“…In older adults, leg muscle mass (22) and chair stand (36) improve following a remote virtually-supervised exercise program. Better lower-limb strength reduces fall risk (35) and preserves functional autonomy (22,63). Thus, morphological adaptations elicited by the training sessions could explain the increased lower-body strength, especially the increased muscle mass (64) and hypertrophic responses (65).…”
Section: Discussionmentioning
confidence: 99%
“…Although the benefits of cardiovascular exercise such as walking, running, cycling or swimming are well known, resistance training has been undervalued in recent decades. In recent years, this type of training has gained relevance and become an interesting topic in clinical settings, especially for older people (Marcos- Pardo et al, 2019;Ramos et al, 2022). Resistance training is recommended because it helps to curb the negative effects of aging, such as functional decline related to sarcopenia, and because it is considered the most effective method to improve muscle mass, strength, functional decline, and power, which are key for counteracting future disability in adults and older people (Botero et al, 2013;Chodzko-zajko, 2014;Ransdell et al, 2021).…”
Section: Health Benefits Of Resistance Trainingmentioning
confidence: 99%